Os impactos da financeirização na inovação: um estudo no setor aeroespacial e de defesa - Alves, Marcel Senaubar (Universidade Federal de São Carlos, 2024)
The blooming predominance of passive investment funds within corporate ownership structures raises concerns about the effects of financialization, particularly the erosion of productive investment in crucial sectors such as Aerospace and Defense (A&D). This sector, characterized by its dual operational nature - civil and military - and significant government interventions, faces unique challenges. This study investigates the complex relationship between financialization and the Research, Development, and Innovation (RD&I) strategies and structures of companies within the A&D sector. The research is conducted in three stages: (1) A bibliometric and systematic literature review to theoretically explore the connection between financialization and innovation; (2) A quantitative analysis of the ownership structure of A&D companies using social network analysis techniques; (3) An evaluation of the economic and innovative performance of the A&D sector through econometric models. The ownership network structure of the A&D sector is revealed to be oligopolistic, indicating that 10 companies hold 61.9% of the invested capital in the sector, with significant influence from financial entities such as BlackRock, Vanguard, State Street, and Capital Research, which control 45.7% of the capital. Furthermore, financialization up to a certain point is associated with improvements in company indicators; however, beyond a certain threshold, further increases in financialization are correlated with a deterioration in company performance. However, it can be concluded that financialization in the sector may be excessive, since there is a relationship between the increase in the degree of financialization and the tendency to reduce its investments in RD&I over time; in addition to investing significantly less. This discussion contributes to the research agenda of Economic Sociology and Finance through empirical research and analysis that emphasize the interaction between financialization and innovation in the A&D sector, highlighting the complexities and contradictions inherent in contemporary financial management within innovation activities.
The impacts of financialization on innovation: a study in the aerospace and defense sector
Keywords: Financeirização; Inovação; Pesquisa e desenvolvimento; Aeroespacial e defesa; Desempenho financeiro; Financialization; Innovation; Research and development; Aerospace and defense; Financial performance; A&D; P&D; R&D; Corporate control; Network analysis; Controle corporativo; Analise de redes; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; ENGENHARIAS